TRIBOTECHNICAL SYSTEM “DEDAL” OF TESTS OF FUEL AND LUBRICANTS FOR ANTI-WORK AND ANTIFRICATION PROPERTIES - Стельмах, О. У.; Сидоренко, О. Ю.; Костюнік, Р. Є. (Proceedings of National Aviation University (archive), 2021)
A system of laboratory tests of fuels and lubricants and additives to them for anti-wear and antifriction properties with appropriate methods of rapid tests of a model sliding tribosystem with a linear contact of constant length, the approbation of which shows high reproducibility.